Synthesis of Composite Material Derived from Soybean Curd and Sludge Containing Fe for Removal of Paracetamol by Heterogeneous Fenton Oxidation - Huynh, Quang Sang; Nguyen, Duy Dat (Journal of Technical Education Science, 2022)
In this study, a composite material (ACS) was successfully synthesized from activated carbon (AC) derived from soybean curd and sludge from the supply water treatment process using FeCl3. Subsequently, the ACS was employed as a heterogeneous catalyst for the degradation of Paracetamol (PRC) in solutions under conditions of the Fenton process. The conditions for synthesizing composite material were evaluated under different temperatures (200 to 900oC) and AC/sludge ratios. Effects of pyrolysis temperature and of reaction parameters (pH, contacting time) were evaluated under batch conditions based on the degradation efficiency of PRC and TOC. PRC and TOC were analyzed using HPLC and TOC instrument. Results showed that the composite material synthesized at 600oC with AC/sludge = 1/1 (w/w) was of the best performance on the removal of PRC (95% after 30 min). At pH 2 and 3, the PRC removal efficiency was 89% and 18% after 15 minutes and 95% and 54% after 30 minutes, respectively, which were significantly higher than those obtained at higher pH values. After 24 hours, the PRC removal efficiency was 99% and the TOC removal efficiency reached 95%. The results indicated that high efficiency was obtained by synthesized material and most of PRC was converted to simple and non-toxic compounds such as CO2 and H2O.